Epidemiology of Absence Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
A population based electroencephalographic study of absence epilepsy in 97 children is reported from the Departments of Neurophysiology and Pediatrics, Goteborg University, Sweden.